Adsorption-Based Laboratory Hazardous Waste Treatment with a Combination of Biochar, Zeolite, and Activated Alumina as an Environmentally Friendly Solution - Akhdiyat, Hendra R.; Sukartono, Sukartono; Jasrodi, Jasrodi; Putra, Hendra Susana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Hazardous and Toxic Waste (B3) from laboratories, especially those containing heavy metals (Hg and Cr) and several physical factors such as pH, TSS, and color, poses a serious threat to the environment if not managed properly. This study aims to estimate the adsorbent for the development of laboratory-scale wastewater treatment equipment based on the adsorption method using biochar, zeolite, and activated alumina. The research method involves preparing adsorbent materials, testing their effectiveness in reducing the content of heavy metal pollutants, and designing a waste treatment device. The combination of biochar, zeolite, and activated alumina was chosen due to their complementary abilities in removing heavy metal content from B3 waste in the Soil Chemistry laboratory. The treatment results showed significant reductions (p < 0.05) in heavy metal (Hg and Cr) levels in laboratory waste. The optimal combination is a formulation of biochar, zeolite, and activated alumina (1:1:1). Innovations in adsorbent technology for processing heavy metal waste in soil chemistry laboratories can be applied and further developed to create a clean and healthy environment.